Depression, Anxiety and Stress Among Frontline Doctors of Covid Hospital in Eastern Nepal (Journal of Psychiatrists' Association of Nepal, 2021)
INTRODUCTION The COVID-19 pandemic has caused several mental health problems including depression, anxiety, and stress. In BPKIHS, junior resident doctors are one of the frontline health care professionals and are vulnerable to mental health problems. This study was undertaken to find out depression, anxiety, and stress in the frontline junior resident doctors (FJRD).METHODOLOGY A web-based cross-sectional study among FJRD was done from 29 August to 28 September 2020 using Depression, Anxiety, and Stress Scale (DASS-21).RESULT Among 168 FJRD, 144(85.7%) responded, and the mean age was 29.6±1.9 years. They were mostly male (56.9%), unmarried (60. 4%), living alone (77.1%), first-year junior residents (43.1%), and had last duty more than 2 weeks(56.9%). Anxiety was seen in 50%; followed by Depression in 38.1%; and Stress in 27.7%. The moderate type of Depression, Anxiety, and Stress was common which were 19.6%, 24.3% and 15.2% respectively. Depression, Anxiety and Stress was more in male (55 to 61.1%), unmarried (60-64%), living alone (76-85%) and first-year residents (37.5-43.6%) but not statistically significant. Depression, Anxiety and Stress were more in those whose last duty more than 2 weeks but statistically significant with Anxiety (p=0.03) only. There was a strong correlation among each other of depression, anxiety and stress (p=